FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN DALAM PENGGUNAAN JASA PENGIRIMAN BARANG - Zumrotun Nafiah; Sopi Sopi (JURNAL STIE SEMARANG, 2022)
The more courier service companies, the more competing to offer their courier services with various advantages that are highlighted as a sustainable competitive advantage. Consumer satisfaction needs to be maintained by meeting consumer expectations. The purpose of this study was to determine the effect of price, the influence of the process, the effect of customer service quality on consumer satisfaction. The population is 1000 consumers of PT. JNE Boyolali, while determining the sample using the Slovin formula and obtained a sample of 91 respondents with a sampling technique, the accidental sampling method. Data collection techniques using questionnaires and documentation. Data analysis method; instrument test, classical assumption test, multiple linear regression analysis, hypothesis test t and F and test the coefficient of determination. The results of the t-test there is a significant effect between price on consumer satisfaction with a value of tcount = 6.096 > ttable 1.662 and a significance probability of 0.000 <0.05. The results of the t-test there is a significant effect between the process on consumer satisfaction with a value of tcount = 3.264 > ttable 1.662 and a significance probability of 0.002 <0.05. The results of the t-test showed the effect of customer service quality on consumer satisfaction with a value of tcount = 2.772 > ttable 1.662 and a significance probability of 0.007 <0.05. F test results obtained with a value of Fcount = 63.004 > Ftable 2.48 and a significance probability of 0.000 < 0.05, so that the model is feasible to use. The coefficient of determination is 0.674 it means that 68.5% variation of changes in consumer satisfaction is explained by price, process, and quality of customer service, while 31.5% is influenced by other research variables. Based on the results of the study concluded that the factors that affect consumer satisfaction in the use of freight forwarding services; price, process, and quality of customer service partially. Suggestions that can be given, the company should pay more attention to pricing, process and service quality related to the process of sending goods, and service quality so that it can even exceed consumer expectations and can make consumers satisfied.